Keterampilan Proses Sains Peserta Didik Melalui Praktikum Pada Materi Sel Kelas Xi Sma Negeri 1 Tapa - Ilvayani; Lilan Dama; Aryati Abdul (Postgraduate, University of Mataram, 2023)
This study aims to determine students' science process skills through practicum method on cell material for class XI IPA of SMA Negeri 1 Tapa. The research method used quasi-experimental, a posttest-only non-equivalent control group design. Data collection was performed through observation sheets and test questions. The data analysis used is the t-test. According to research conducted in class XI IPA 1 using the practicum method, students in the experimental class had an average science process skill score of 79%. In contrast, students in the control class, which did not use the practicum method, had an average of 55%. Therefore, the science process skills of students in the experimental class are higher than those in the control class due to the use of the practicum method. Teachers guide students in activities during the learning process by asking open-ended questions that spark a discussion. Students are therefore required to be active, creative, and able to collaborate during the learning process to meet the learning objectives and understand the concepts being taught easily.